Notes on Bio-History: Michel Foucault and the Political Economy of Health - Chiaramonte, Xenia (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
In October 1974, Foucault gave three lectures in Rio de Janeiro on the archeology of the cure. This piece will comment on the first two, published a few years later in France with the original titles: Crise de la médicine ou crise de l’antimédicine? and La naissance de la médicine sociale. Bio-history is the term Michel Foucault initially uses – in the second lecture – to refer to the effect of the strong medical intervention at the biological level that started in the eighteenth century and has left a trace that is still visible in our society. It is on this occasion that Foucault introduces the concept, or rather the prefix “bio-” in his analysis, and it is here – as my reflections intend to demonstrate – that we may trace the original meaning of a term that today seems rather abused and find a valuable analytical framework for a cogent approach to the relationship between medicine and power dynamics.